Hubungan Pengetahuan dan Motivasi Terhadap Keberhasilan Pengobatan Pasien Tuberculosis Paru - Rahmadhani, Velia (Jurnal Ayurveda Medistra, 2024)
Introduction: Treatment success decreased by 4% between 2013 and 2016. This requires further analysis. Knowledge and motivation are among the predisposing factors for treatment success. However, research results still show a gap where knowledge does not significantly correlate with treatment success, while some respondents show negative motivation. This study assessed the relationship between knowledge and motivation for treatment success in patients with pulmonary TB.Methods: This study used a quantitative design with a cross-sectional method of 72 respondents at Menteng Mitra Afia Hospital. Patients included in this study had a stable condition as seen through the measurement of vital signs, and had been on treatment for 6 months as seen through the patient's treatment sheet. Data analysis was performed using the chi-square statistical test.Results and Discussion: The results showed a significant relationship between knowledge and motivation in the success of treatment in patients with pulmonary tuberculosis. Knowledge is influenced by the information received. The more information received, the better knowledge the patient will have, while motivation is needed to encourage patients to be actively involved in disease control.Conclusion: This study shows a significant relationship between knowledge and motivation in treatment success in patients with pulmonary tuberculosis.